Visuo-attentional activity of neurons in the subthalamus in Parkinson's disease. Issue 3 (March 2016) - Sieger, T.; Serranová, T.; Růžička, F.; Vostatek, P.; Wild, J.; Št'astná, D.; Bonnet, C.; Novák, D.; Růžička, E.; Urgošík, D.; Jech, R.
Abstract : Objective: The subthalamic nucleus (STN) is an important motor and non-motor hub. Animal studies suggest that the STN is also involved in perception, however evidence in humans is missing. We analyzed the visuo-attentional activity of STN neurons in Parkinson's disease (PD) patients. Methods: Extracellular neuronal activity and electrooculography was recorded during deep brain stimulation surgery from 12 awake PD patients (mean age 54.4 (SD 8.1) years) during presentation of 24 photographs, each shown for 2 s and preceded by a black screen. The action potentials elicited by watching photographs vs. black screen were compared using bootstrap. Results: Of the 122 neurons detected, 34 were eye movement-related and excluded. The activity of 45 (51%) of the remaining 88 neurons was stimulus-specific ( P < 0.05): the photographs decreased activity in 14 neurons (which were in the dorsal STN), and increased activity in 31 neurons (with no spatial preference). Conclusions: The STN contains a surprisingly high ratio of neurons possibly involved in visuo-attentional processes. Key message: Neurons of the STN are involved in visual perception and processing.